2020
DOI: 10.13189/ujer.2020.082520
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Study Habits and the Academic Achievement of High School Pupils

Abstract: A descriptive survey was conducted to assess the correlation between study habits and academic achievements among high school pupils, in a nominated school at Alappuzha District, Kerala. Disproportionate stratified random selection was used to pick out 180 high school pupils. Information was collected by using the socio demographic questionnaire, Modified M. Mukhopadhaya's and D. N. Sansanwal's study habits inventory and the review of previous year progress reports. The data were tabulated and examined by mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The findings revealed that a very high positive correlation was found between study habits and academic achievement of students studying in Govt secondary schools of Sambalpur district, which emerged to support earlier findings of Premlaxmi (2012); Kaur and Pathania (2015); Siahi and Maiyo (2015); Arora (2016); Alavi et al (2017); Looyeh et al (2017); Numan and Hasan (2017); Rabia et al (2017); Jafari et al (2019); John et al (2020) and Sasi and Anju (2020). On the other hand, the results of this study did not match with the findings of Nonis and Hudson (2010); Lawrence (2014); Silverrajoo and Hassan (2018), since they found no significant relationship between reading habits and academic performance.…”
Section: Discussion Of Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The findings revealed that a very high positive correlation was found between study habits and academic achievement of students studying in Govt secondary schools of Sambalpur district, which emerged to support earlier findings of Premlaxmi (2012); Kaur and Pathania (2015); Siahi and Maiyo (2015); Arora (2016); Alavi et al (2017); Looyeh et al (2017); Numan and Hasan (2017); Rabia et al (2017); Jafari et al (2019); John et al (2020) and Sasi and Anju (2020). On the other hand, the results of this study did not match with the findings of Nonis and Hudson (2010); Lawrence (2014); Silverrajoo and Hassan (2018), since they found no significant relationship between reading habits and academic performance.…”
Section: Discussion Of Resultssupporting
confidence: 81%
“…Meta-analysis result revealed that plethora of studies have been conducted ubiquitously to examine the correlation between reading habits and educational attainment of learners at various levels of education and concluded the result that a significant positive correlation exists between reading habits and academic achievement (Alavi, Lesani, & Mahdavinia, 2017;Arora, 2016;Jafari, Anghaei, & Khatony, 2019;John, Bulus, & Tangsom, 2020;Kaur & Pathania, 2015;Looyeh, Masoule, Chehrzad, & Leili, 2017;Numan & Hasan, 2017;Premlaxmi, 2012;Rabia et al, 2017;Sasi & Anju, 2020;Siahi & Maiyo, 2015), whereas others found no significant relationship (Lawrence, 2014;Nonis & Hudson, 2010) some also found significant difference (Rabia et al, 2017;Vasu & Venkatarathanam, 2017) while some others found no significant difference (Bhan & Gupta, 2010;Gudaganavar & Halayannavar, 2014) further, some researchers used study habits as a predictor to enhance academic performance (Allen, Lerner, & Hinrichsen, 1972;Broni & Hogrey, 2010;Crede & Kuncel, 2008;Numan & Hasan, 2017;Robres, Andraze, Ortega, & Ramajo, 2021). In the light of the present reviews, the researcher found that academic achievement is being highly simulated by learners' reading habits.…”
Section: Rationale Of the Studymentioning
confidence: 99%
“…On the variables of study habits and examination anxiety, there is a preponderance of studies on their relationship with academic achievement but very few , if any, have considered their association with examination integrity or academic integrity. For instance, in a study by Asha and Anju (2020) on the relationship between study habits and academic achievement of high school students, it was found that study habits had very strong positive relationship with academic performance hence it was concluded that "a rise in study habits score will also raise the academic achievement score among high school pupils." By extension, as found in the present study, study habits also has very strong relationship with examination integrity.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that there is a relationship between study habits and academic achievement (Jafari, 2019;Rabia et al, 2017;Sasi & Anju, 2020). Although not every learning strategy or study habit produces useful results in terms of academic achievement, it would be expected that students with good study habits in general are better performers than students with poor study habits (Nonis & Hudson, 2006).…”
Section: Online Study Habitsmentioning
confidence: 99%